The Concept of I’jāz Al-Qur’ān in KH. A. Musta’in Syafi’i’s Exegesis: An Interdisciplinary Study between Qur’anic Hermeneutics and Science - Farina Fikria Aulia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2026)
This article examines the concept of i’jāz al-Qur’ān in Tafsir Aktual by KH. A. Musta’in Syafi’i, positioning it within the framework of contemporary Indonesian Qur’anic exegesis oriented toward the contextualization of revealed meaning. This study aims to describe the formulation of the i’jāz concept developed by KH. Musta’in, identify the most dominant aspect of i’jāz in his exegetical practice, and analyze the hermeneutic approach employed in explaining the miraculous nature of the Qur’an to modern society. This research employs a descriptive qualitative approach with hermeneutic methods and field study. Data were obtained through textual analysis of Tafsir Aktual published in Bangsa Online, in-depth interviews as a means of clarification and interpretation validation, and literature review of contemporary tafsir and ‘ulūm al-Qur’ān scholarship. Data analysis was conducted using a thematic hermeneutic approach through dialogue between the textual horizon and the readers’ social context. The findings indicate that KH. A. Musta’in Syafi’i formulates i’jāz al-Qur’ān integratively, emphasizing two dominant aspects: i’jāz balāghī and i’jāz ‘ilmī. The balāghī aspect is evident in his analysis of diction, metaphor, linguistic structure, and morphological functions of the Qur’an, while the ‘ilmī aspect is manifested in reflective dialogue between āyāt kawniyah and modern rational knowledge without reducing the Qur’an to a scientific textbook. The hermeneutic approach employed is dialogical, communicative, and pedagogical, rendering the exegesis not merely informative but also socially transformative. This study concludes that Tafsir Aktual by KH. Musta’in Syafi’i represents a contemporary exegetical model that successfully revitalizes the concept of i’jāz al-Qur’ān in a moderate, contextual manner relevant to the needs of the Muslim community in the digital era.